Effect of Spironolactone on Exercise Tolerance and Arterial Function in Older Adults with Heart Failure with Preserved Ejection Fraction. Issue 11 (19th May 2017) - Upadhya, Bharathi; Hundley, William G.; Brubaker, Peter H.; Morgan, Timothy M.; Stewart, Kathryn P.; Kitzman, Dalane W.
Abstract : Objectives: To evaluate the effects of an aldosterone antagonist on exercise intolerance in older adults with heart failure and preserved ejection fraction (HFpEF). Design: Randomized, placebo‐controlled, double‐blind trial. Setting: Academic medical center, Winston‐Salem, North Carolina. Participants: Older adults (N = 80, aged 71 ± 1; 80% female) with stable compensated HFpEF and controlled blood pressure (BP). Measurements: Participants were randomized into a 9‐month treatment of spironolactone 25 mg/d vs placebo. Assessments were peak exercise oxygen consumption ( V O2 ), 6‐minute walk test, Minnesota Living with Heart Failure Questionnaire (MLHFQ), cardiac magnetic resonance imaging, Doppler echocardiography, and vascular ultrasound. Results: Seventy‐one participants completed the trial: 37 in the spironolactone group and 34 in the placebo group. Adherence according to pill count was excellent (spironolactone 95%, placebo 97%). Mean spironolactone dose was 24.3 ± 2.9 mg/d and was well tolerated. Spironolactone significantly reduced systolic and diastolic BP at rest and peak exercise. At 9‐month follow‐up, baseline‐adjusted peak V O2, the primary outcome, was 13.5 ± 0.3 mL/kg per minute in the spironolactone group versus 13.9 ± 0.3 mL/kg per minute in the placebo group (adjusted mean difference −0.4 mL/kg per minute; 95% confidence interval = −1.1–0.4 mL/kg per minute; P  = .38). The 95% confidence intervals of spironolactone's effect on peak V O2 (−8.2% to 3.2%) excluded a clinically significant beneficial effect. There were also no significant differences in 6‐minute walk distance, arterial stiffness, left ventricular (LV) mass, LV mass/end‐diastolic volume, or MLHFQ score. Conclusion: In older adults with stable compensated HFpEF, 9 months of spironolactone 25 mg/d was well tolerated and reduced BP but did not improve exercise capacity, quality of life, LV mass, or arterial stiffness.